Coordination Behavior and Reactivity of α‐Heterosubstituted Trimethylsilylalkynes at Titano‐ and Zirconocene1. Issue 34 (6th November 2014) - Altenburger, Kai; Baumann, Wolfgang; Spannenberg, Anke; Arndt, Perdita; Rosenthal, Uwe
Abstract: The coordination behavior of the α‐donor‐atom‐substituted (trimethylsilyl)alkynes OC4 H8 N–C≡C–SiMe3 (2 ), EtO–C≡C–SiMe3 (3 ), and Me2 P–C≡C–SiMe3 (4 ) towards group 4 metallocene generators [Cp2 Ti(η 2 ‐btmsa)] (1a ), [Cp2 Zr(py)(η 2 ‐btmsa)] (1b ), and [Cp*2 Ti(η 2 ‐btmsa)] (1c ) [Cp = η 5 ‐cyclopentadienyl; btmsa = bis(trimethylsilyl)acetylene; py = pyridine; Cp* = η 5 ‐pentamethylcyclopentadienyl] was investigated. By using1a and1b, metallacyclopropenes were obtained for alkyne2, a titanacyclopentadiene for alkyne3, and dimeric‐stabilized metallacyclopropenes for alkyne4 . Employing the sterically demanding metallocene1c resulted in monomeric metallacyclopropenes for alkynes3 and4 . The reactivity of the obtained complexes towards CO2 and acetone was explored as well, thus leading to regioselective formation of metallafuranones and metalladihydrofurans. Abstract : Adding a donor atom (D) in the α position of the triple bond of an alkyne causes a strong polarization, which is retained in the metallacyclopropenes formed by reaction with early‐transition metallocene fragments (Ti, Zr). This polarization in turn governs the regioselectivity for the further insertion of alkynes and carbonyls such as acetone.